Studi Kecerdasan Linguistik Mahasiswa dalam Menyampaikan Khutbah Jumat - Polem, Muhammad; Akbarjono, Ali; Dalima, Hengki (JPT : Jurnal Pendidikan Tematik, 2022)
In delivering religious treatises such as Friday sermons, it is not only the duty of preachers, preachers, or clerics, but anyone has the right to remind each other in nahi munkar actions, including Islamic Religious Education Students. In essence, it is true that PAI students are forged to become professional teachers. But in the social context, the general public doesn't care about that, so like it or not, PAI students must be able to become preachers. In fact, not all students are able to become reliable preachers, this is due to the lack of students' linguistic intelligence, especially in delivering Friday sermons. The purpose of this study was to determine the linguistic intelligence of students in delivering Friday sermons, describe obstacles/obstacles and describe things that students must improve or improve regarding their linguistic intelligence in delivering Friday sermons at the mosque in Selebar District, Bengkulu City. This study uses a qualitative approach, field studies and qualitative descriptive methods. The result of this study is that the linguistic intelligence of students in delivering Friday sermons at the Selebar Subdistrict mosque, Bengkulu City is quite good. This is marked by the courage to deliver Friday sermons, the sermons delivered have met the requirements and pillars, even though students do not have high self-confidence, and the delivery of sermons is still often stammered or has the impression of being in a hurry. But besides all that, over time, the researcher believes and believes that the student will be really good at being a Friday preacher.